Evaluation of Surface Microhardness of Artificial White Spot Lesion Treated with Three Different Treatment Approaches. An in-vitro study - Aya A. Kh. Al-Taee; Afrah Kh. Al-Hamdany (University of Mosul, College of Dentistry, 2024)
Aims: The current study aims to compare the impact of three different treatment approaches on the surface microhardness of the enamel of third molar teeth. Materials and Methods: An in vitro study was done on fifty extracted impacted third molars. All samples were immersed in solutions of pH cycle for 10 days (demineralizing solution for 3 hours, remineralizing solution for 20 hours, and artificial saliva for 30 minutes twice daily). Then the samples were divided randomly into 5 groups according to enamel surface treatment, group1: Colgate (containing Arginine) toothpaste, group2: GC (containing Casein phosphopeptide-amorphous calcium phosphate (CPP-ACP)-tooth mousse, group 3: Sensodyne (containing NovaMin) toothpaste group 4: distilled water and group 5: pH cycle solutions. The microhardness numbers were calculated from the length of the indentation on the enamel surface, the indentation length was determined microscopically with 70X magnification. An ANOVA was constructed (value P ≤ 0.05) followed by Duncan's post -hoc test for comparisons of mean values. Results: there were significant differences among the study groups with respect to Vickers microhardness (VMH) mean values of samples. The lowest value was for the control group after the pH cycle followed by the Colgate (containing Arginine) group and the highest value was for the control group before the pH cycle followed by the Sensodyne (containing NovaMin) group. Conclusions: Sensodyne (containing NovaMin) toothpaste is more effective in restoring the hardness of artificial WSLs when compared with GC (containing CPP-ACP) and Colgate (containing Arginine) toothpaste